INTELLIGENT NIGHT VISION SYSTEM FOR AUTOMOBILE BASED ON COMPUTER VISION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In today’s world where we are witnessing second generation of automotive night vision systems uses near cameras in combination with pedestrian detection systems. This system is intended towards the increasing drivers’ visibility in the night by focusing attention of driver by showing all pedestrian on a display provided in the car. This helps in analyzing the imminent situation by providing and more and accurate information of all objects or persons in the path. Thus, the next generation of night vision systems needs to integrate an additional warning component which signals to the driver only the relevant objects, that is, all objects on the road or near the road. Such systems needs to detect objects more reliably and sooner and has to provide information about the object’s position. Rain, fog and wet road way surfaces dramatically alter visibility of driver. It reduces the visibility of drivers’ water on pavement increases forward reflection while reducing backward reflection, resulting in glare to oncoming vehicles. Camera detects the oncoming vehicle and sensor automatically adjust headlight glare.